2015
DOI: 10.1530/eje-15-0519
|View full text |Cite
|
Sign up to set email alerts
|

Pegvisomant in combination with long-acting somatostatin analogues in acromegaly: the role of the GH receptor deletion of exon 3

Abstract: Background: Doses of the GH receptor (GHR) antagonist pegvisomant (PEGV) that normalize insulin-like growth factor 1 (IGF1) levels vary widely among acromegaly patients. Predictors for PEGV response are baseline IGF1 levels, sex, body weight and previous radiotherapy. A GHR polymorphism lacking exon 3 (d3-GHR) is frequent in the general population. The influence of d3-GHR on PEGV responsiveness in acromegaly is unclear. Objective: To assess the influence of d3-GHR on IGF1 levels and PEGV responsiveness in acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Two studies, indeed, reported a lower required PEGV dose during disease control in acromegaly patients with the d3-GHR genotype [16,24] . However, more recent studies in larger acromegaly cohorts could not confirm these findings [25,26] . These contradictory reports on the influence of d3-GHR in acromegaly patients regarding PEGV treatment responses and the PEGV doses required to normalize IGF-I levels motivated us to conduct a systematic review of the literature to identify studies examining this question and to perform a meta-analysis.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Two studies, indeed, reported a lower required PEGV dose during disease control in acromegaly patients with the d3-GHR genotype [16,24] . However, more recent studies in larger acromegaly cohorts could not confirm these findings [25,26] . These contradictory reports on the influence of d3-GHR in acromegaly patients regarding PEGV treatment responses and the PEGV doses required to normalize IGF-I levels motivated us to conduct a systematic review of the literature to identify studies examining this question and to perform a meta-analysis.…”
Section: Introductionmentioning
confidence: 88%
“…One original study [16] was excluded as the majority of the patients were included in a larger more recent study, which was already part of this metaanalysis [25] . Finally, we included 3 published original studies and 1 conference abstract describing one relevant acromegaly cohort [24][25][26]29] . All 4 selected papers included data of both requested outcomes: (1) lowest IGF-I level expressed as ULN during PEGV treatment and (2) the required PEGV dose to achieve the lowest IGF-I level.…”
Section: Literature Searchmentioning
confidence: 99%
“…Additionally, some studies evaluated the GHR polymorphisms as a possible cause of a lower response to the drug, with conflicting results regarding whether patients who present the exon-3 deleted GHR (d3GHR) had a better response to pegvisomant (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, a large multicenter study (111 patients) and a study from our group did not find a difference in the response rates to pegvisomant treatment between patients with the d3GHR and those with the flGHR 31,104 . Additionally, another study described no difference in the response rates to combination therapy with pegvisomant and fg-SRL in patients with the different isoforms of GHR 105 . Therefore, current knowledge suggests that d3GHR is not a biomarker of response to pegvisomant.…”
Section: Biomarkers Of Treatment Response In Acromegalymentioning
confidence: 98%